A new species of Deinodryinus Perkins, 1907 (Hymenoptera, Dryinidae) from Minas Gerais, Brazil - Martins, André Luis (Zootaxa, 2015)
Deinodryinus pratapolensis sp. nov. is described and illustrated. This species was collected by yellow pan trap, in a gallery forest at Pratápolis (Minas Gerais, Brazil).